Retrospective cohort study of decompression illness in Lumut and effect of early treatment - Jamharee, Fazriyati (2016)
Decompression illness is a rare condition among divers, aviators and astronauts in which bubbles form in blood and tissues following a reduction in environmental pressure. It has wide clinical manifestation and gives a great challenge to Emergency Physician to differentiate decompression illness from other diving related injury. Early detection of decompression illness is crucial as this will determine the type of treatment based on the severity. Severe decompression illness is a denominator for poor prognosis and warrant a definitive treatment with hyperbaric oxygen therapy. Fast access to the treatment will be a good indicator for the recovery. This study aimed to determine recovery outcome in relation to the time to treatment from the onset of symptoms. Methodology This was a retrospective cohort study of all patients diagnosed as decompression illness and treated with hyperbaric oxygen therapy in Hospital Angkatan Tentera Lumut since January 2000 to December 2010. Data was collected from registration book and medical records in the recompression hyperbaric chamber. All data entered into SPSS version 21.0.1 for further descriptive statistic and analysis. Chi square test, univariate and multiple logistic regressions was used to identify significant variables (p≤0.25) in comparison of complete recovery between early TTR group (within 6 hours) and delayed TTR group (more than 6 hours). Results A total of 96 cases reviewed and 16 patients (16.7%) were able to get early access for the recompression therapy whereas 80 patients (83.3%) had delayed treatment of more than 6 hours from symptoms onset after surfacing. All different times of treatment was tested and significantly found that early treatment of less than 6 hours had better recovery status in getting complete resolution of symptoms (OR 8.33, P value 0.050). Conclusion Recompression should be administered early as it resulted in better outcome recovery by limiting disability in divers associated with DCI and prompt complete resolution of symptoms.